Fur Processing in Raižiai in the 20th Century: Craft and Image - Jonas Mardosa (Lietuvos Istorijos Studijos)
In Lithuania, fur processing craft used to change depending on the social, cultural and even political context of the development of the state and the nation. In the Tatar community of Raižiai several craftsmen were engaged in fur processing. The artisans were in direct contact with the fur craftsmen working in Butrimonys and the surrounding villages. In this way, the fur processing craft habitat was formed, the centre of which was Raižiai. The article examines the fur processing craft in Raižiai and its surroundings on the basis of archival data and ethnological literature. The forms of fur processing craft transfer between gene rations and their change over time are examined. The aim of the article is to reveal the essence of the Tatar famous business in Raižiai in the context of the history of Lithuanian crafts and to highlight the specific features of the life of the local Tatar community.